2020
DOI: 10.1111/jnu.12590
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression of Nurses in a North West Province in China During the Period of Novel Coronavirus Pneumonia Outbreak

Abstract: Purpose To investigate the anxiety and depression levels of frontline clinical nurses working in 14 hospitals in Gansu Province, China, during this period. Design A cross‐sectional survey was conducted online between February 7 and 10, 2020, with a convenience sample of 22,034 nurses working in 14 prefecture and city hospitals in Gansu Province, located in northwest China. Methods A self‐reported questionnaire with four parts (demographic characteristics, general questions related to novel coronavirus‐infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
1
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 28 publications
6
95
1
13
Order By: Relevance
“…Some of the studies that recruited more than one cadre reported that specific HCWs were at higher risk of developing mental health problems. A number of studies found that nurses were more likely to develop PTSD ( Tang et al 2017 , Barello et al 2020 , Song et al 2020 ), anxiety ( Han et al 2020 , Huang et al 2020 ), stress (Hui Wang et al 2020), and burnout ( Tolomiczenko et al 2005 ), whereas one study ( Austria-Corrales et al 2011 ) reported that resident pulmonologists were at higher risk of burnout.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies that recruited more than one cadre reported that specific HCWs were at higher risk of developing mental health problems. A number of studies found that nurses were more likely to develop PTSD ( Tang et al 2017 , Barello et al 2020 , Song et al 2020 ), anxiety ( Han et al 2020 , Huang et al 2020 ), stress (Hui Wang et al 2020), and burnout ( Tolomiczenko et al 2005 ), whereas one study ( Austria-Corrales et al 2011 ) reported that resident pulmonologists were at higher risk of burnout.…”
Section: Resultsmentioning
confidence: 99%
“…The overall pooled point estimates of depression reported by the 62 studies [ 19 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , 34 , 35 , 37 , 39 , 42 , 43 , 45 , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , 90 , 91 , [94] , [95] , [96] , [99] , [100] , [101] , [102] , [103] , [105] , [106] , [107] , [108] ] varied between 9% and 89% ( Fig. 4 : forest plots).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three studies examined education levels in association with distress. Only eight studies, six conducted during the COVID-19 pandemic ( 27 , 66 , 70 , 89 , 94 , 149 , 151 ), along with studies conducted during the Ebola outbreak ( 76 ), and the MERS outbreak ( 81 ) found that HCW with higher educational levels reported significantly lower psychological distress. Twenty-two studies found that education level was not predictive of psychological distress among HCW working during the MERS or the COVID-19 outbreaks ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%